PERANCANGAN PEMBANGKIT LISTRIK TENAGA SURYA ATAP DI HOTEL NOVOTEL UBUD RESORT & SUITE BALI - Arta Saputra, I Wayan; Setiawan, I Nyoman; Ariastina, Wayan Gede (Jurnal SPEKTRUM; Vol 8 No 3 (2021): Jurnal SPEKTRUM, 2021)
The service quality of a hotel is supported by a sustainable supply of electrical energy. Electrical energy at the Novotel Ubud Resort & Suite Bali hotel is supplied from PT. PLN. Source Power plant PT. PLN predominantly uses fossil fuels that are less environmentally friendly. The solution to this problem is to use renewable fuels to reduce environmental pollution and as a source of electrical energy at the Novotel Ubud Resort & Suite Bali hotel. This study aims to design a rooftop solar power plant at the Novotel Hotel Ubud Resort & Suite Bali. The results of the simulation of PLTS electrical energy production using the HOMER application. The feasibility of rooftop solar power plants using the NPV, PI and DPP methods. Based on the data obtained, the Novotel Ubud Resort & Suite Bali Hotel consists of five flat and pyramidroofed buildings with a total roof area of 2723 m2. This study uses 576 solar modules with a total power output of 236.16 kWp and uses 3 inverters with a capacity of 80 kW. The results of the HOMER simulation show that the annual electrical energy production from PLTS is 377,083 kWh. From the feasibility of PLTS has an NPV value of Rp. 633,125,923, the PI value is 1.25 and the DPP value is 13.8 years. The results of this design can be said to be feasible because the NPV value is positive and is able to reverse the initial cost of PLTS for 13.8 years from the assumption for 25 years.